Recent research on Health Care Management - Steffen Fleßa (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2013)
[Preface] Health Care Management is a global mission, i.e., neither diseases nor health care concepts can be addressed adequately with a limited focus on one particular country. For instance, multi-resistant bacteria do not respect national borders but are a challenge in Poland as well as in Germany. Any attempt to solve this problem in one country only is doomed to failure as bacteria will re-invade from the other country. At the same time, health care concepts developed in one country will likely be an innovation seedling for other nations. For instance, individualized medicine is likely to challenge the existing paradigm of health care provision. Although this concept is strongly fostered at the University of Greifswald, it might soon be of highest importance at the University of Stettin. Health Care Management is global! For this reason, I am delighted to have the opportunity to present a series of papers on recent developments of health care management at the University of Stettin and learn from the experiences of my colleagues at this center of research. As scientists we share methodology and paradigms, and we unite in the fight for better health for the population of our nations. Health Care Management has much to offer to the health care systems, providers and programs. Based on evidence, efficient solutions can be sought to tackle life-threatening diseases and to improve the quality of life of millions of people. It is a privilege to share these insights with our Polish colleagues. And it is my sincere hope that this cooperation will bear fruit. This booklet provides an overview of the papers presented in Stettin, May 2013. The papers do not focus on methodology but on decision-making relevance. For methodological insights, the reader is asked to contact the authors. Every author is responsible for their paper, but we conjointly submit this booklet to the reader hoping that they will be inspired by one of the most challenging scientific fields: Health Care Management.
Keywords: 330